Estabilização de Skyrmions magnéticos em multicamadas de Pt/Co/Ta depositadas em nanodomos - Silva, Denilson Toneto da (2020)
Magnetic skyrmions are non-trivial spin textures that resist external disturbances and are promising candidates for next generation magnetic recording devices. However, a major challenge in the realization of devices based on skyrmions is the stabilization of ordered ar-rangements of these spin textures under ambient temperature and zero applied field condi-tions. Among the materials that have skyrmions, the multilayer of ferromagnetic materials (Co) interspersed with heavy metals (Pt and Ta), with strong spin-orbit coupling, have inte-resting properties, as they favor the Dzyaloshinskii-Moriya (DMI) interaction, which is a anti-symmetric exchange interaction that tilts the spins of neighboring layers and helps to stabili-ze skyrmions. The objective of this thesis is to observe and study the stabilization of skyr-mions in Pt/Co/Ta films and also deposited on nanomodulated substrates. The formation and stabilization of magnetic skyrmions in self-organized hexagonal nanodome arrays is de-monstrated for the first time. The Pt/Co/Ta multilayers were fabricated by sputtering, with different Co thicknes-ses, and thus it was possible to modulate the perpendicular anisotropy. A FORC diagram technique, obtained from Hall Effect measurements, was used to determine the magnetic fields that should be applied to nucleate skyrmions, and thus stabilize skyrmions at zero fi-eld. Magnetic force microscopy images of the continuous films and nanodomes with 100 and 200 nm showed stable skyrmions in the zero field, and in the case of nanodomes, these are organized according to the topography of the nanostructures. Micromagnetic simulations of films and nanodomes were compared with experiments to determine the correlation of the domain textures with the topography of the samples.